Crumple-recoverable electronics based on plastic to elastic deformation transitions - Roh, Yeonwook; Lee, Seunggon; Won, Sang Min; Hwang, Suhyeon; Gong, Dohyeon; Kim, Changhwan; Hong, Insic; Lim, Daseul; Kim, Hyeongseok; Kim, Minho; Kim, Baekgyeom; Kim, Taewi; et al. (Nature Electronics, 2024)
Crumpling is potentially a quick and efficient way to pack sheet-like electronic devices at a high compression ratio. However, crumpling is not applicable to conventional electronic devices because disordered and irreversible plastic deformation can occur, which affects electronic function. Here we report crumple-recoverable electronics based on heterogenous integration of silver nanowires, a shape memory polymer and an elastomer. Our approach is inspired by the emergence process of butterfly wings, which have variable stiffnesses as they unfold, and allows the mechanical properties of sheet-like devices to transform via thermal modulation from an elastic (2 MPa) state suitable for smoothing out wrinkles formed during crumpling to a plastic (1,315 MPa) state suitable for free-standing operation. We use the approach to create touch panels (7 cm by 7 cm) that can be crumpled and packed into capsules (1 ml volume), and then used as a flat and smooth surface for reliable touch sensing after unpacking.
Keywords: Butterfly wings; Electronic functions; Electronics devices; High compression ratio; Shape memory polymers; Sheet-like; Silver nanowires; Smoothing outs; Thermal modulation; Variable stiffness